1986
DOI: 10.1159/000138181
|View full text |Cite
|
Sign up to set email alerts
|

Acetyltransferase in Humans: Development and Tissue Distribution

Abstract: Acetyltransferase with p-aminobenzoic acid (PABA) as substrate was investigated in the cytosolic fraction of the placenta, liver, adrenals, lungs, kidneys, intestine from human fetuses and the liver, lungs, kidneys and intestinal mucosa from adult subjects. All tissue specimens assayed catalyzed the acetylation of PABA at a significant rate. The activity (expressed as nmol of product formed/min/mg protein; mean ± SE) was 1.10 ± 0.59 in the fetal liver, 0.66 ± 0.04 in the placental and 3.87 ± 0.53 in the adult … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(47 citation statements)
references
References 10 publications
3
44
0
Order By: Relevance
“…However, on the basis of the available literature it seems that the drugmetabolizing enzymes generally are well ex pressed in the kidney. This is particularly true for conjugating enzymes such as glucuronyl transferase [11,42], acetyltransferasc [11,34], glutathionetransfcrase [11,31], sulphotransferase [11,35], and thiomcthyltransferase and thiopurinemethyltransferase [present work].…”
Section: Discussionmentioning
confidence: 99%
“…However, on the basis of the available literature it seems that the drugmetabolizing enzymes generally are well ex pressed in the kidney. This is particularly true for conjugating enzymes such as glucuronyl transferase [11,42], acetyltransferasc [11,34], glutathionetransfcrase [11,31], sulphotransferase [11,35], and thiomcthyltransferase and thiopurinemethyltransferase [present work].…”
Section: Discussionmentioning
confidence: 99%
“…Expression of human NAT1 www.intechopen.com has been detected in adult liver, bladder, digestive system, blood cells, placenta, skin, skeletal muscles, gingiva (Dupret & Lima, 2005), mammary tissue, prostate, and lung by a number of methods (Sim et al, 2008). A notable difference between the two isoenzymes is the presence of NAT1 activity in fetal and neonatal tissue, such as lungs, kidneys, and adrenal glands (Pacifici et al, 1986). By contrast, NAT2 is not evident until about 12 months after birth (Pariente-Khayat et al, 1991).…”
Section: N-acetyltransferasesmentioning
confidence: 99%
“…Studies had shown expression of both NAT1 and NAT2 in human colon (Kirlin et al, 1991;Turesky et al, 1991;Ilett et al, 1994), intestine (Hickman et al, 1998) and widespread tissue distribution of human NAT1 and NAT2 mRNA (Windmill et al, 2000;Boukouvala and Sim, 2005). Although extrahepatic expression of N-acetyltransferase activities have been reported in humans (Pacifici et al, 1986), rat (Hein et al, 1991a), mouse (Chung et al, 1993;Stanley et al, 1997;Sugamori et al, 2003) and Syrian hamster (Hein et al, 1991b(Hein et al, , 1994a) models, substrates were not selective for NAT1 and NAT2. NAT2-dependent ABP-and BNA N-acetyltransferase activities have been reported in human urinary bladder Frederickson et al, 1992Frederickson et al, , 1994Pink et al, 1992;Badawi et al, 1995).…”
Section: Phenotypic Expression Of the Nat2 Polymorphismmentioning
confidence: 99%